The detection of SSRs from the terrier dog normal and tumoral mammary gland tissue EST Libraries - Ömeroğlu Ulu, Zehra; Çelik, Merve; Ulu, Salih; Özdemir Özgentürk, Nehir (Afyon Kocatepe Üniversitesi)
Dogs share a common environment with humans and knowledge of the specific dog breed diseases is very useful in developing a model for human cancer studies. ESTs represent part of the transcribed genome of an organism and are an important resource for identifying microsatellites. Simple Sequence Repeats (SSRs), or microsatellites, which contain repetitive DNA sequences, are among the most powerful genetic markers known. The development of EST-SSRs has become a fast, efficient, and low-cost option for genomic studies. In this study, to determine SSRs from EST libraryof mammary gland tissue of the Terrier dog that has 2304 ESTs; SSRIT and IMEx software, which have web-based versions and are easily accessible, were used. SSRIT finds motifs from 2 to 10 base lengths and adjusts the minimum number of repeats by eliminating single nucleotide motifs. IMEx finds perfect and imperfect microsatellites separately. It can find motifs of different lengths from 1 to 6 and the minimum number of repeats can be set. In addition, the appropriate primer for the desired SSR region can be designed. The 2, 3, 4, 5 and 6 nucleotide motifs were found for normal tissue ESTs whereas 5 nucleotide motifs were not found for tumoral tissue ESTs

Köpekler, insanlarla ortak bir çevreyi paylaşır ve belirli köpek ırklarının hastalıkları hakkında bilgi, insan kanser çalışmaları için bir model geliştirmede çok yararlıdır. EST'ler, bir organizmanın transkribe edilen genomunun bir parçasını temsil eder ve mikrosatellitleri tanımlamak için önemli bir kaynaktır. Tekrarlayan DNA dizilerini içeren Basit Dizi Tekrarları (SSR'ler) veya mikrosatellitler, bilinen en güçlü genetik belirteçler arasındadır. EST-SSR'lerin gelişimi, genomik çalışmalar için hızlı, verimli ve düşük maliyetli bir seçenek haline gelmiştir. Bu çalışmada, 2304 EST içeren Terrier köpeğin meme bezi dokusunun EST koleksiyonundan SSR'lerin belirlenmesi için; Web tabanlı sürümleri olan ve kolayca erişilebilen SSRIT ve IMEx yazılımları kullanılmıştır. SSRIT, 2 ila 10 baz uzunluğundaki motifleri bulur ve tekli nükleotid motiflerini ortadan kaldırarak minimum tekrar sayısını ayarlar. IMEx mükemmel ve kusurlu mikrosatellitleri ayrı ayrı bulur. Farklı uzunluklarda 1 ile 6 arasındaki motifleri bulabilir ve minimum tekrar sayısı ayarlanabilir. Ek olarak, istenen SSR bölgesi için uygun primer tasarlanabilir. Normal doku EST'leri için 2, 3, 4, 5 ve 6 nükleotidli motifler bulunurken, tümörlü doku EST'leri için 5 nükleotidli motif bulunamamıştır.
Terrier köpek normal ve tümörlü meme dokusu EST Kütüphanelerinden SSR’ların belirlenmesi
Keywords: SSR; EST-SSR; Terrier; Cancer; Dog